Meningkatkan Komunikasi Antar Pribadi melalui Layanan Bimbingan Kelompok dengan Teknik Modeling Simbolis - ghozali, noor halida fitriawati; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2016)
This study was conducted based on the phenomenon that occurs in Class IX J SMPN 3 Ungaran less have good interpersonal communication skills. The purpose of this research is to improve interpersonal communication skills through group guidance with symbolic modeling techniques. Population in this research is class student of SMPN 3 Ungaran IXJ totaling 32 students with a sample of 10 students were taken using purposive sampling. Data collection method used is the psychological scale interpersonal communication and observation. Data were analyzed using Wilcoxon test match pairs. The results showed prior to obtaining the guidance of the group with symbolic modeling techniques interpersonal communication skills of students included in the criteria was, and after obtaining the guidance of the group with the criteria of symbolic modeling techniques student interpersonal communication becomes high. It shows that the group guidance with symbolic modeling techniques can improve students' interpersonal communication.